The INFREP Network: Present Situation and Recent Results - Biagi, P. F. (2019)
VLF/LF (20 - 300 kHz) radio waves propagation is affected by different factors such as meteorological conditions, solar bursts and geomagnetic activity. At the same time, variations of some parameters in the ground, in the atmosphere and in the ionosphere occurring during the preparatory phase of earthquakes can produce disturbances in the propagation of the previous signals along their radio paths: these disturbances are the radio precursors. Since 2009, several VLF/LF radio receivers have been installed throughout Europe in order to realize a European (VLF/LF) radio network for studying the VLF/LF radio precursors of earthquakes, called the INFREP network. In this paper, at first the description of the present situation of the INFREP network is presented, that is: the location of the receivers, the location of the VLF/LF transmitters whose signal is sampled, the daily download of the data collected by the receivers on the INFREP server and the method of data analysis used in order to individuate possible radio precursors. Then the results obtained on the occasion of recent (2016-2017) seismic activities which occurred in the “sensitive” zone of the INFREP network are presented. The first case examined is the October 30, 2016 earthquake with Mw = 6.5, which occurred in Central Italy, near Norcia small town; this earthquake was preceded by a strong shock (Mw = 5.9) which occurred 4 days before. The second case presented is the strong (Mw = 6.7) offshore earthquake which occurred on July 20, 2017, near the coast of Turkey and Kos island (Greece) and the third case is the August 8, 2017 earthquake with Mw = 5.0, which also occurred near the coast of Turkey and Kos island (Greece). In all the previous cases radio anomalies were revealed in some radio signals collected by the receiver located in Cyprus. The influence of causes different from seismicity as geomagnetic activity and solar burst, meteorological conditions, malfunction of the receiver and/or the transmitters has been examined and none convincing connections appeared. So, the possibility that the previous anomalies are radio precursors of the earthquakes seems realistic. Finally, some discrepancy of some of these anomalies with respect to the general peculiarities of the radio precursors is presented and discussed.